Big Data and Strengthening MSMEs After the Covid-19 Pandemic (Development Studies on Batik MSMEs in East Java) - Putri, Rumanintya Lisaria; Hidayat, Sarif; Suprapto; Wahyono, Eko; Sriyono; Rahmawati, Lili (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2023)
This research aims to analyze the effect of online business on economic growth in Java Island, segment and optimize aspects that support the development of internet business in the locus of Java Island, especially East Java Province, and complement it with a The existence of social.The method used is a combination of 5 techniques, namely regression analysis, thematic map visualization, clustering, spatial analysis, and text mining. This research has major implications for the development of MSMEs because MSMEs have succeeded in implementing e-commers in their sales and this greatly affects economic growth. Through the support of other analyses, it will also be known that the factors that support economic growth are more complete. The results show that online business affects the economic growth of provinces in Java. Online business businesses need to continue to be optimized by improving the quality of HDI and web networks, especially in the development priority areas of East Java Province. Programs related to the advanced economy need to be encouraged to align changes in the order of society with MSME activities in adapting to the e-digitalization period. This research has major implications for the development of MSMEs because MSMEs have succeeded in implementing e-commers in their sales and this greatly affects economic growth. Through the support of other analyses, it will also be known that the factors that support economic growth are more complete. This condition is more specific to developing countries and Covid-19 Pandemi.